EFEKTIVITAS KINERJA BADAN PERMUSYAWARATAN DESA (BPD) TERHADAP PEMERATAAN PEMBANGUNAN DESA DI DESA GROGOL KECAMATAN GIRI KABUPATEN BANYUWANGI - Dharmawan, Gilang; Wilujeng, Sri; Jatu Permatasari, Safrieta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2025)
The low participation of the BPD in supervision and development planning, which results in unequal benefits for the community.This study aims to evaluate the extent to which the BPD contributes to achieving village development goals and to understand the factors influencing its performance effectiveness.The research methodology uses a qualitative approach with purposive sampling techniques to determine relevant informants.Data collection was conducted through interviews, observations, and document analysis.The research results indicate that the BPD has not yet functioned optimally in absorbing community aspirations and conducting effective oversight.The performance of the BPD tends to be administrative in nature, without active involvement in the development process.The discussion reveals that the dominance of the village head hinders the role of the BPD, causing the functions of oversight and community participation to not run well.The limited understanding of BPD members regarding their duties and functions also becomes a hindrance.The conclusion of this study emphasizes that although village development is proceeding on schedule, the effectiveness of the BPD's performance remains low.